A global plastid phylogeny of the fern genus Asplenium (Aspleniaceae). (11th July 2019) - Xu, Ke‐Wang; Zhang, Liang; Rothfels, Carl J.; Smith, Alan R.; Viane, Ronald; Lorence, David; Wood, Kenneth R.; Chen, Cheng‐Wei; Knapp, Ralf; Zhou, Lin; Lu, Ngan Thi; Zhou, Xin‐Mao; et al.
Abstract: The infrageneric relationships and taxonomy of the largest fern genus, Asplenium (Aspleniaceae), have remained poorly understood. Previous studies have focused mainly on specific species complexes involving a few or dozens of species only, or have achieved a large taxon sampling but only one plastid marker was used. In the present study, DNA sequences from six plastid markers ( atpB, rbcL, rps4, rps4 ‐ trnS, trnL and trnL‐F ) of 1030 accessions (616 of them newly sequenced here) representing c . 420 species of Asplenium (60% of estimated species diversity), 16 species of Hymenasplenium, three Diplaziopsidaceae, and four Rhachidosoraceae were used to produce the largest genus‐level phylogeny yet for ferns. Our major results include: (i) Asplenium as broadly circumscribed is monophyletic based on our inclusion of representatives of 32 of 38 named segregate genera; (ii) 11 major clades in Asplenium are identified, and their relationships are mostly well‐resolved and strongly supported; (iii) numerous species, unsampled in previous studies, suggest new relationships and numerous cryptic species and species complexes in Asplenium ; and (iv) the accrued molecular evidence provides an essential foundation for further investigations of complex patterns of geographical diversification, speciation and reticulate evolution in this family.